The world of Disney - Gill, David William John, 1961- (Oxford)
viii, 142 sayfa
Keywords: “Dr. John Disney (1779-1857) was the benefactor of the first chair in archaeology at a British university. He also donated his major collection to the University of Cambridge. The sculptures continue to be displayed in the Fitzwilliam Museum. The Disney family traced its origins back to the Norman invasion of England, and the family home was at Norton Disney in Lincolnshire. Disney’s father, the Reverend John Disney DD (1746-1816) left the Church of England to become a minister at the Unitarian Essex Street Chapel in London. A major sponsor of the chapel was Thomas Brand-Hollis of The Hyde, Essex, who bequeathed the house and his Grand Tour collection (formed with Thomas Hollis) on his death in 1804 to the Reverend John Disney. Disney inherited part of the classical collection of his uncle and father-in-law Lewis Disney-Ffytche, owner of the 18th century pleasure gardens, Le Désert de Retz, outside Paris. Disney’s brother-in-law was Sir William Hillary, founder of the RNLI. Disney was instrumental in the creation of the Chelmsford Museum through the Chelmsford Philosophical Society, and the formation of the Essex Archaeological Society” --